2017
DOI: 10.3847/1538-4357/aa689f
|View full text |Cite
|
Sign up to set email alerts
|

First Discoveries of z > 6 Quasars with the DECam Legacy Survey and UKIRT Hemisphere Survey

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 51 publications
(82 reference statements)
0
41
0
Order By: Relevance
“…We also include some quasars, which are not in the SDSS DR7 or DR12 catalog. A high redshift quasar catalog with 437 z > 4.5 (called the BONUS high redshift sample) was constructed from the literature (Table 1 and Table 3 in Wang et al (2015) and references therein; Table 7 in Bañados et al (2016) and references therein; Jiang et al 2016;Yang et al 2017;Wang et al 2017). …”
Section: Spectroscopically Identified Quasar Samplementioning
confidence: 99%
See 1 more Smart Citation
“…We also include some quasars, which are not in the SDSS DR7 or DR12 catalog. A high redshift quasar catalog with 437 z > 4.5 (called the BONUS high redshift sample) was constructed from the literature (Table 1 and Table 3 in Wang et al (2015) and references therein; Table 7 in Bañados et al (2016) and references therein; Jiang et al 2016;Yang et al 2017;Wang et al 2017). …”
Section: Spectroscopically Identified Quasar Samplementioning
confidence: 99%
“…The 5σ pointsource magnitude limits in g, r, and z will be roughly 24.7, 23.9, and 23.0 mag. With depths of 1.5 − 2.5 mag fainter than in the SDSS, the DELS will be useful in searching for fainter quasars than the SDSS spectroscopic quasars, and also high redshift quasars (Wang et al 2017). In this work, we use the three band (grz) photometry from the DECaLS DR3.…”
Section: Decals Photometrymentioning
confidence: 99%
“…In fact, current Lyα forest measurements at z > 4 ( Viel et al 2013a;Iršič et al 2017;D'Aloisio et al 2018b) provide constraints on the power at the relevant scales (10 −3 > k > 10 −1 s km −1 , 10 −1 > k > 10 h/Mpc) and therefore may already tell us something about the effects of inhomogeneous reionization on the IGM at these redshifts. Moreover the past several years have seen a dramatic fivefold increase in the number of z 6 quasars from deep wide-field optical/IR surveys (Willott et al 2010;Bañados et al 2014;Venemans et al 2015b,a;Wang et al 2017). The ongoing spectroscopic follow-up of these objects (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…15 We do not consider the quasars VDES J0224-4711 (z 6.50 = ; Reed et al 2017), DELS J104819.09-010940.2 (z 6.63 = ; Wang et al 2017), and J1429-0104 (z 6.80; = Matsuoka et al 2017), which were reported during the final stages of the preparation of this manuscript.…”
Section: Introductionmentioning
confidence: 99%